Pengaruh Earning per Share (EPS) dan Return on Equity (ROE) terhadap Harga Saham pada Sektor Perbankan BUMN yang Terdaftar di Bursa Efek Indonesia Periode 2016–2022 - Indah, Sri (Universitas Nahdlatul Ulama Surabaya, 2024)
Good company value is very useful because it is able to attract investor interest in the company, showing the company's ability to generate profits and increase share prices so that it can support shareholder profitability. The aim of this research is to determine the effect of Earning Per Share (eps) and Return on Equity (roe) on share prices in the state-owned banking sector listed on the Indonesian stock exchange for the 2016-2022 period. The research carried out was research using quantitative methods. The research carried out by researchers relates to numbers and calculations will be carried out from the data that has been obtained by downloading financial reports on the official website of the Indonesian Stock Exchange (BEI) with an observation period from 2016 to 2022. The data collection technique used by researchers is a documentation technique. The data analysis technique in this research uses Descriptive Data Analysis, Multiple Linear Regression Test. The results of this research show that the Earning Per Share (EPS) variable partially has a positive effect on the stock price variable and has a significant effect on the stock price variable, while the Earning Per Share (EPS) and Return on Equity (ROE) variables simultaneously have an effect on the stock price variable.